Developmental relations between ADHD symptoms and bullying perpetration and victimization in adolescence - Eisner, Manuel (2020)
It has previously been hypothesized that individuals with elevated attention deficit hyperactivity disorder (ADHD) symptoms are at greater risk of bullying perpetration and victimization. Using autoregressive latent trajectory models with structured residuals (ALT-SR) and four waves (ages 11, 13, 15, and 17) of longitudinal data from the normative z-proso study (n = 1526, 52% male), we evaluated the developmental relations between ADHD and bullying using both self- and teacher-reported ADHD symptom data. Analyses suggested that ADHD symptoms primarily increase the risk of bullying perpetration, with a within-person effect of ADHD symptoms on bullying perpetration symptoms identified across ages 13-15 (β = .13) and ages 15-17 (β = .19) based on self-reported ADHD symptoms and a similar effect identified across ages 11-13 (β = .24) and 13-15 (β = .29) based on teacher-reported inattention symptoms. There were also some indications of reciprocal effects and effects involving victimization that merit further exploration in future research. Results imply that the content of bullying intervention and prevention programs should take account of ADHD symptoms to ensure that those with elevated symptoms can benefit as much as their typically developing peers. This will involve addressing bullying perpetration that may reflect impulsive/reactive aggression and impaired social skills rather than instrumental aggression. Further, programs should go beyond classical curriculum/classroom-based delivery to ensure that individuals with elevated ADHD symptoms can be successfully engaged